PROSPECTS FOR DIGITIZATION OF MANAGEMENT ACCOUNTING (Conferencea, 2023)
This article discusses the digitalization of financial accounting in the digital economy, management problems, as well as directions for development to eliminate them. The necessity, possibility and expediency of introducing specific (calculation) methods into the work of managers is noted. Within the framework of the task, the possibility of creating and developing a parametric model of a social system operating in an active environment is shown , using appropriate techniques, tools, including computer programs for automating management activities and modeling models. In business, it can be used in decision-making systems and decision support systems, as well as in training to develop decision-making skills.